Trauma‐Related Correlates of Alcohol Use in Recently Deployed OEF/OIF Veterans. Issue 3 (20th May 2013) - Capone, Christy; McGrath, Ashlee C.; Reddy, Madhavi K.; Shea, M. Tracie
<x xml:space="preserve">Abstract</x> The co‐occurrence of posttraumatic stress disorder (PTSD) and alcohol use disorders (AUDs) is well documented. Little is known about the factors that contribute to alcohol use and the development of AUDs among military personnel following deployment. The primary aim of this study was to examine trauma‐related correlates of alcohol use in recently deployed Operation Enduring Freedom/Operation Iraqi Freedom veterans. Members of the Rhode Island National Guard and Army Reserves (N = 238) completed an in‐person, initial assessment an average of 6 months postdeployment. Multiple regression analyses examined predictors of drinking outcomes (combat exposure, total PTSD symptoms, and PTSD symptom clusters) after accounting for gender, age, and history of AUD. Results indicated that total PTSD symptoms, but not combat exposure, significantly predicted alcohol use at the initial assessment. When PTSD symptom clusters were considered separately, reexperiencing symptoms (Cluster B) were the strongest predictor of total alcohol use (B = 3.58, p = .002) and heavy drinking episodes (B = 0.31, p = .005). Implications for these findings include early identification of risk factors that could lead to the development of AUDs, and the importance of integrated treatment approaches for co‐occurring PTSD and AUD among veterans postdeployment.